2022
DOI: 10.3390/molecules27154982
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Prodigiosin as a Bioactive Compound in Nanocomposite Applications

Abstract: Bionanocomposites based on natural bioactive entities have gained importance due to their abundance; renewable and environmentally benign nature; and outstanding properties with applied perspective. Additionally, their formulation with biological molecules with antimicrobial, antioxidant, and anticancer activities has been produced nowadays. The present review details the state of the art and the importance of this pyrrolic compound produced by microorganisms, with interest towards Serratia marcescens, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 121 publications
(129 reference statements)
0
7
0
Order By: Relevance
“…However, the anticancer mechanisms of action and the specific molecular targets of PG are quite diverse [28,29]. Similar to PHBV, PG can be produced sustainably using bacterial fermentation [30,31]. It is also pH-responsive [32].…”
Section: Introductionmentioning
confidence: 99%
“…However, the anticancer mechanisms of action and the specific molecular targets of PG are quite diverse [28,29]. Similar to PHBV, PG can be produced sustainably using bacterial fermentation [30,31]. It is also pH-responsive [32].…”
Section: Introductionmentioning
confidence: 99%
“…Though the exact mechanism of antibacterial action for PDG remains obscure, independent studies using different target organisms revealed affecting pH, disruption of the plasma membrane, degradation of DNA and ROS generations as generic mode of bactericidal action of PDG (Araujo et al 2022). Also, the mode of action seems to vary between different groups of bacteria as disruption of cell wall and subsequent lysis has been speculated as the major event in Gram positive bacteria, while in the case of Gram-negative bacteria, it affect metabolism and gene expression (Araujo et al 2022). Observation from the present study indicates that QQ activity of PDG might also be a possible mechanism against Gram negative organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Prodigiosin has recently received interest due to its antioxidant activity (which improves the immune system), its antimicrobial activity against bacterial, fungal and yeast species [ 15 , 27 , 28 , 29 ], and its antiproliferative effect on cancer cells [ 29 , 30 , 31 ]. Antimicrobial activity (although low level) against some bacterial strains was demonstrated in agar diffusion tests in the present study, as it was against other members of Enterobacteriaceae under experimental cheesemaking conditions.…”
Section: Discussionmentioning
confidence: 99%